Homologous tropomyosins from vertebrate and invertebrate: Recombinant calibrator proteins in functional biological assays for tropomyosin allergenicity assessment of novel animal foods. Issue 1 (11th October 2019) - Klueber, Julia; Costa, Joana; Randow, Stefanie; Codreanu‐Morel, Françoise; Verhoeckx, Kitty; Bindslev‐Jensen, Carsten; Ollert, Markus; Hoffmann‐Sommergruber, Karin; Morisset, Martine; Holzhauser, Thomas; Kuehn, Annette
Abstract: Background: Novel foods may provide new protein sources for a growing world population but entail risks of unexpected food‐allergic reactions. No guidance on allergenicity assessment of novel foods exists, while for genetically modified (GM) crops it includes comparison of sequence identity with known allergens, digestibility tests and IgE serum screening. Objective: As a proof of concept, to evaluate non‐/allergenic tropomyosins (TMs) regarding their potential as new calibrator proteins in functional biological in vitro assays for the semi‐quantitative allergy risk assessment of novel TM‐containing animal foods with mealworm TM as an example. Methods: Purified TMs (shrimp, Penaeus monodon ; chicken Gallus gallus ; E coli overexpression) were compared by protein sequencing, circular dichroism analysis and in vitro digestion. IgE binding was quantified using shrimp‐allergic patients' sera (ELISA). Biological activities were investigated (skin testing; titrated basophil activation tests, BAT), compared to titrated biological mediator release using humanized rat basophil leukaemia (RBL) cells. Results: Shrimp and chicken TMs showed high sequence homology, both alpha‐helical structures and thermal stability. Shrimp TM was stable during in vitro gastric digestion, chicken TM degraded quickly. Both TMs bound specific IgE from shrimp‐allergic patients (significantly higher for shrimp TM), whereas skin reactivity was mostly positive with only shrimp TM. BAT and RBL cell assays were positive with shrimp and chicken TM, although at up to 100‐ to 1000‐times lower allergen concentrations for shrimp than chicken TM. In RBL cell assays using both TM as calibrators, an activation of effector cells by mealworm TM similar to that by shrimp TM confirmed the already reported high allergenic potency of mealworm TM as a novel protein source. Conclusions & clinical relevance: According to current GM crops' allergenicity assessment, non‐allergenic chicken TM could falsely be considered an allergen on a weight‐of‐evidence approach. However, calibrating allergenic potency in functional BAT and RBL cell assays with clinically validated TMs allowed for semi‐quantitative discrimination of novel food protein's allergenicity. With TM calibration as a proof of concept, similar systems of homologous protein might be developed to scale on an axis of allergenicity.